2022
DOI: 10.3390/ijerph19073894
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Carbon in China’s Export Trade: A Multi Region Input-Output Analysis

Abstract: With the rapid growth of China’s export trade and increasing pressure of domestic carbon emission reduction, the issue of carbon embodied in export trade has attracted increasing attention from academic circles. This paper has constructed a calculation model for embodied carbon in China’s export trade by using the multi-region input-output model and the international input-output data from the World Input-Output Database (WIOD) database in order to calculate the amount of embodied carbon. Our objective is to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…The integration of expectations, service quality, and satisfaction in a model reveals their mechanism, highlighting the mediating effect between students’ expectations and their satisfaction. The United Nations Statistical Office (CPC), the World Trade Organization (WTO), and the International Organization for Standardization (ISO) classify higher education as a service industry (W. Yang et al, 2022), with higher education institutions embracing the concept of students as consumers (Kotler & Levy, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…The integration of expectations, service quality, and satisfaction in a model reveals their mechanism, highlighting the mediating effect between students’ expectations and their satisfaction. The United Nations Statistical Office (CPC), the World Trade Organization (WTO), and the International Organization for Standardization (ISO) classify higher education as a service industry (W. Yang et al, 2022), with higher education institutions embracing the concept of students as consumers (Kotler & Levy, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…An opinion poll among Austrian employees revealed that men have a more favorable attitude towards teleworking than females, and gender and age stereotypes have no effect on the 41% of Austrian employees who worked remotely during the pandemic [86][87][88]. At the end of 2020, the share of males (employees) working from home in the total employment in the EU reached 11.2%, while that of females reached 13%.…”
Section: Work-life Balancementioning
confidence: 99%
“…Referring to the calculation methods of Weixin Yang et al [38,39] and the evolutionary game of Ying Zhu et al [40], especially the evolutionary game analysis of urban traffic environment governance made by Jun yi Liu et al [41], this paper attempts to construct a multiparty dynamic game model to deconstruct the daily behavior of vendors and analyze the final evolutionary stable strategy of urban governance.…”
Section: Literature Reviewmentioning
confidence: 99%